Impact of the central refractive index dip of fibers on high-power applications - An, Yi; Chen, Xiao; Ren, Yankun; Wu, Hanshuo; Huang, Liangjin; Pan, Zhiyong; Jiang, Zongfu; Zhou, Pu (Frontiers in Physics, 2023)
Central refractive index dip is a common phenomenon in the fibers fabricated by the modified chemical vapor deposition (MCVD) technology, which is the main fabrication technique for high-power laser fibers. In this paper, we present a numerical analysis of the dip effect on high-power-related parameters for the first time, to the best of our knowledge. Three aspects including mode field parameter, beam quality, and bending performance are studied under different dip parameters and bending radii. It is found that the dip is possible to increase the effective mode area and the bending loss, which offers a flexible way to suppress the non-linear effects and filter the higher-order modes by optimizing the dip parameters. Besides, different from the mode area and bending loss, beam quality exhibits an interesting trend when the dip radius increases. The results could facilitate a comprehensive understanding of the dip fiber properties, which also offer guidance to evaluate and design the fiber with central refractive index dip for high-power applications.